The Influence of Initial Capital, Business Duration, Working Hours, and Number of Workers on the Income of Traders at Tugu Market, Bandar Lampung City - Antikasari, Piji Dewi; Asliana, Endang; Puspitasari, Endah Yuni (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Economic growth in developing countries is often driven by the informal sector, particularly traditional market trading, which plays a critical role in creating employment and supporting low-income communities. In Indonesia, many individuals turn to informal trading due to limited access to formal jobs and education. The purpose of this research is to analyze how internal business elements namely starting capital, length of business operation, hours worked, and workforce size affect the income levels of traders in Tugu Market, Bandar Lampung. The research is motivated by fluctuating income levels in the market and inconsistent findings in existing literature. Using a quantitative approach and survey method, data were collected from 194 traders selected through the Slovin formula from a total population of 378. Structured questionnaires, direct observations, unstructured interviews and subsequently analyzed using multiple linear regression along with classical assumption testing. The findings reveal that both initial capital and the length of time the business has been operating have a substantial effect on income levels, whereas working hours and number of workers do not. These results underscore the significance of adequate funding and prior experience. It is recommended that local governments prioritize capital support and practical business training, supported by ongoing evaluation to enhance income sustainability in the informal sector.